The small islands and the continental country: Flows between Cape Verde and Brazil - Lobo, Andrea (2023)
This article aims to contribute to mapping and reflecting on the mobility of black populations from the African continent to South America. As is known, such routes have been (and still are) continued over time, but with very different specificities, rhythms and characteristics. Based on data on the mobility of Cape Verdeans to South American countries, focusing on the case of Brazil, we intend to demonstrate how this flow is part of broader movements of the Cape Verdean diaspora to the Americas and is connected to historical dynamics on both sides of the Atlantic, which have shaped the strategies, rhythms and characteristics of such flows over time.